(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: Studies assessing the impact of loss of consciousness (LOC) on prognosis of subarachnoid hemorrhage (SAH) has been limited. Objective: This scientific assessment was done to determine the effect of LOC on outcome of SAH. Methodology: This hospital based observational study was done in Department of Neurology of Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2018 to December 2018. Patients with the diagnosis of SAH admitted in the in-patient wards of Neurology, Neurosurgery and Internal Medicine were taken as study population. The patients were divided in two groups with either presence (B) or absence of loss of consciousness (A). Group B was further subdivided into 3 subgroup depending admission WFNS scale grades (BI= WFNS II &III, BII=WFNS IV and BIII=WFNS V). Follow up was done in the stroke clinic, outpatient department of Neurology or by telephone interviews of patients, caregivers or family members. Outcome was measured by modified Rankin Scale (mRS). Result: A total of 75 patients were divided into group A and Group B. Six (8.0%) patients died during hospital stay, 6 died after 3 months. All those died during hospital stay were from group B. At 3 months, 16(21.3%) patients were lost during follow up. In group A at discharge 28.6% patients had poor outcome whereas 36% of patients in group B had poor outcome. Within group B most of the patients having poor outcome were in subgroup BIII (75.0%) compared to 33.0% cases in BI (p=0.023). About 16.7% cases in group A had poor outcome at 3 months and 75.0% cases in Group BIII. Furthermore, 8.3% patients died in Group A, however, 25.0% died in Group BIII. WFNS grade (IV or V) had statistically significant influence on poor outcome among patients having LOC (adjusted Odds ratio is 2.20, p=0.04 and 95% CI 1.03–4.71). Conclusion: Loss of consciousness at onset of SAH is an important marker for p oor outcome. Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 20-24